A comparison of rt-PA thrombolysis guidelines between China and the USA: are changes needed?. (January 2015) - Xu, Jing; Zhang, Yongjin; Wei, Hongyu; Xu, Yan; Wang, Min; Cai, Zenglin; Li, Xiaomin
<x content-type="archive" xml:space="preserve">Abstract</x> Background and purpose: Thrombolytic treatment criteria vary significantly between China and the USA. We reviewed current intravenous (IV) thrombolytic therapy practices in China and the USA to determine the most appropriate. Methods: We conducted a systematic review of studies that used IV recombinant tissue plasminogen activator (rt-PA) therapy in China and the USA published between January 1950 and April 2012. Results: Literature search identified 17 American and 9 Chinese studies with a total of 2545 subjects. We found a significantly lower mortality rate in the US data compared with China (8% versus 13%; Chi-square = 24·412, P < 0·001). Our meta-regression analysis uncovered significant factors influencing mortality including male sex, hypertension, high cholesterol, smoking, and onset to treatment time (all P < 0·05). There were significantly more favorable outcomes in China than in the USA (61% versus 49%, Chi-square = 19·159, P < 0·001). No prior history of stroke and shorter onset to IV time were also significantly associated with a favorable outcome (P < 0·05). Conclusions: Onset to IV time is critical for reducing mortality and improving favorable outcomes. We suggest Chinese acute ischemic stroke treatment guidelines be revised to include an increase in the age limit of 80 years, removing contraindications such as a history of previous sever heart, liver, and kidney dysfunction, and placing more emphasis on physician expertise.